2021
DOI: 10.1039/d1ea00067e
|View full text |Cite
|
Sign up to set email alerts
|

Multiple site ground-based evaluation of carbonaceous aerosol mass concentrations retrieved from CAMS and MERRA-2 over the Indo-Gangetic Plain

Abstract: Objectives: (a) ground-truthing of black and organic aerosol mass simulated by CAMS and MERRA-2, (b) identification of different atmospheric processes that propagated errors in these reanalysis datasets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…However, authors in the literature have already reported disagreements between ground‐measured and satellite‐derived particulate matter data. [ 31–34 ] At Central and Eastern China, [ 32 ] seasonality in the MERRA‐2 ( PM 10 and all PM components) reanalysis was observed when comparing to ground measurements, in which performed better in summer than winter. The possible reasons of this seasonality are the simulation bias of meteorology (i.e., overestimation of wind and the boundary layer height) and different levels of precipitation, humidity, and air temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, authors in the literature have already reported disagreements between ground‐measured and satellite‐derived particulate matter data. [ 31–34 ] At Central and Eastern China, [ 32 ] seasonality in the MERRA‐2 ( PM 10 and all PM components) reanalysis was observed when comparing to ground measurements, in which performed better in summer than winter. The possible reasons of this seasonality are the simulation bias of meteorology (i.e., overestimation of wind and the boundary layer height) and different levels of precipitation, humidity, and air temperature.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that Jaén has low levels of PM on average comparing to the studies in India, China, and Mexico. [31][32][33]…”
Section: Particulate Matter Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, despite scavenging, the MAE of BC and BrC for the fog droplet associated events was found to be increased, indicating that aqueous processing can significantly enhance their absorption capacity. Furthermore, a recent study reported the discrepancy in the OC and BC data obtained from reanalysis data, which was attributed to the variable emission sources, secondary formation, and aging of aerosols …”
Section: Emerging Important Role Of Brown Carbonmentioning
confidence: 99%
“…The absorption properties of carbonaceous aerosols are one of the most critical parameters for the quantification of aerosol radiative forcing . Still, there is significant uncertainty in the estimation of black carbon (BC) radiative forcing, mainly as a result of its mixing with other complex non-refractory organic and inorganic chemicals. Previously, several modeling and laboratory studies have provided a clue that the mixed BC particles absorb more strongly than the bare/pure BC aerosols, often called the lensing effect. , The core–shell Mie theory is often used to estimate coated BC absorption properties by assuming a spherical BC core surrounded by uniform coating materials . However, some ambient studies have reported that the core–shell approximation overestimates the absorption enhancement primarily as a result of the unequal distribution of coating materials, varying thickness of the outer shell, non-spherical core, and heterogeneity associated with particle-to-particle composition. , In contrast, some other studies have reported significant enhancement of BC as a result of coating. , Overall, there are significant spatial and temporal variations reported for absorption enhancement of BC as a result of varying the mixing state, thus calling for more in situ observations …”
Section: Introductionmentioning
confidence: 99%